A web-based system for managing student attendance and assessment submissions: an SDLC waterfall model approach - Mahlan, Siti Balqis; Othman, Jamal; Shamsuddin, Maisurah; Mohamed Yusoff, Syarifah Adilah; Othman, Zalina (UiTM Cawangan Perlis, 2025)
University lecturers handle numerous tasks, including tracking student attendance, managing multiple assessment submissions, handling online tests and quizzes, as well as providing timely evaluations of assessments. Currently, these processes are manually managed, which can be time consuming and inefficient due to the absence of an integrated web-based application system. For example, students often submit their assignments or project papers through cloud storage links provided by lecturers. However, the lack of standardization in file naming frequently forces lecturers to spend additional time renaming hundreds of files before they can begin the grading process. This paper presents a proposed solution in the form of an integrated web-based application system designed to automate and streamline critical tasks like attendance tracking, assignment submission, and evaluation, serving as a comprehensive, one-stop solution for lecturers. SDLC (System Development Life Cycle) Waterfall Development Approach was applied as a method of system construction. HTML and PHP were employed for its implementation and handling of diverse functionalities. To assess the system’s effectiveness, it was tested over one academic semester with the participation of 111 degree and diploma students at Universiti Teknologi MARA, Perlis branch. Findings revealed that the system significantly simplified the attendance logging process and streamlined assignment submissions, as perceived by the students. In parallel, lecturers reported that the system facilitated a more efficient grading process, allowing them to return assessments promptly and allowing students to access their marks quickly and easily. Overall, the integration of these automated modules helped reduce bureaucratic inefficiencies, allowing lecturers to perform their duties with greater efficiency and less stress. Positive feedback from students also highlighted a desire for this system to be expanded to other courses, alongside suggestions for further enhancements to improve functionality.